Rytų aukštaičių vilniškių pakraštinių šnektų kirčiavimo ypatumai - Urbanavičienė, Jolita (Baltistica, 2006)
ACCENTUATION PECULIARITIES OF PERIPHERAL SUBDIALECTS OF EAST HIGHLANDERS OF THE VILNIUS DIALECTThe paper sets out to overview the accentuation features of the Svirkos subdialect (Adutiškis parish, district of Švenčionys) located in the area of frequent Lithuanian-Slavic contacts. The features include the relics of oxytone and barytone accentuation, columnal accentuation, the double-peaked and secondary stress types.The accentuation system of the Svirkos subdialect has been found to be rather close to other peripheral subdialects of the Vilnius dialect (Gervėčiai, Dieveniškės etc.). The parameters that help identify the closeness of the subdialects are as follows: 1) well-preserved barytone and oxytone accentuation patterns; 2) the impact of Slavic languages on prosody (violations of the Saussure-Fortunatov law, the stress placement is not related to the tone of the word, columnal accentuation). The author suggests that the double-peaked stress and the secondary phonological stress in northern dialects are stronger (in the area of the Utena dialect), whereas in southern dialects (southern highlanders) weaker than in peripheral subdialects of the Vilnius dialect. Secondary non-phonological stresses, though optional, perform important functions: contribute to the rhythmic arrangement of the phrase (rhythmic stress), make up for the loss of ending or help preserve the full ending (morphemic stress). The accentuation systems of Vilnius dialect idioms are less different than their vocalisms.
Keywords: dialektologija; rytų auštaičiai; akcentologija